Food for thought? Experimental evidence on the learning impacts of a large-scale school feeding program in Ghana - Aurino, Elisabetta; Gelli, Aulo; Adamba, Clement; Osei-Akoto, Isaac; Alderman, Harold (International Food Policy Research Institute, 2018)
There is very limited experimental evidence of the impact of large-scale, government-led school meals programs on child educational achievements in Sub-Saharan Africa. We address this gap by reporting treatment effects from a nationwide randomized trial of the Government of Ghana’s school feeding program (GSFP) on children’s math and literacy, cognition (problem-solving ability and working memory), and composite scores of overall attainments. Based on the government’s plans to re-target and scale up the GSFP, food insecure schools and related communities across the country were randomly assigned to school feeding. After two years of implementation, program availability led to moderate increases in test scores for the average pupil in school catchment areas, ranging between 0.12 and 0.16 standard deviations. Analysis focusing on per-protocol population subgroups unveiled substantial heterogeneity: school feeding led to remarkable learning and cognitive gains for girls, poorest children, and children from the northern regions. Program effects were at least twice as large as for the average child. Increases in enrolment, grade attainment, and shifts in time use toward schooling time constituted potential mechanisms for impact. We conclude the program combined social protection with equitable human capital accumulation, thus contributing to the imperative of “learning for all” set in the Sustainable Development Goals.